Analisis Pengaruh Digital Presenter terhadap Penjualan pada E-commerce - Rizal Eka Saputra N. (Asosiasi Ahli Administrasi Indonesia, 2022)
The purpose of this study is to see the effect of live streaming hosts on online product sales in Bandung City and Regency. Respondents came from millennials from Bandung City and Regency who had made online purchases from e-commerce live streaming. This study uses descriptive quantitative methods, validity and reliability tests, normality tests, and data analysis using simple linear regression. The sample in this research is 100 respondents. Data collection was carried out by distributing questionnaires to respondents via the Google Form. The results of this study indicate that the role of the live streaming hosthas an effect on product sales in Bandung City and Regency.